MicroRNA and vascular smooth muscle cell phenotype: new therapy for atherosclerosis? - Zhang, Chunxiang (BioMed Central, 2009)
MicroRNAs (miRNAs) represent a class of small, non-coding RNAs that negatively regulate gene expression via degradation or translational inhibition of their target mRNAs. Recent studies have identified that miR-145 is the most abundant miRNA in normal arteries and vascular smooth muscle cells (VSMCs), and its expression is significantly downregulated in dediffer-entiated VSMCs and atherosclerotic arteries. miR-145 plays a critical role in modulating VSMC phenotype. Because phenotypic modulation of VSMCs is an initial cellular event in the development of atherosclerosis, miRNAs, and miR-145 in particular, may represent new therapeutic targets for atherosclerosis.